45‐4: Advanced Structure and Process for Dual‐Cell LCD. Issue 1 (28th June 2021) - Huang, Hua; GU, Xin; Wang, Guoqiang; Li, Haixu; Han, Jiahui; Li, Shulei; Ma, Yong; Kang, Zhao; Li, Duohui; Zhao, Chengtan; Guo, Kang; Liu, Zhen; et al.
Abstract : This paper described the advanced process for Dual‐Cell LCD. Through the built‐in POL, Dual‐Cell structure of four glasses was simplified to three glasses. Key technologies were WGP on cell for middle polarizer, low temperature cell process, high alignment accuracy for main cell and sub array. The results showed that contrast was greater than 10, 000, the moiré and H mura is invisible to the naked eye due to smaller 0.5mm gap between main cell and sub array(1.0mm gap for four‐glass dual cell), the high alignment accuracy(x, y≤5um, θ ≤0.005°) for main cell and sub array.